Di-2-ethylhexylphthalate May Be a Natural Product, Rather than a Pollutant - Aurelio Ortiz; Estibaliz Sansinenea (Journal of Chemistry)
Di-2-ethylhexylphtalate is an ester of phthalic acid that has been used as plasticizer in many materials. Due to the extended use, it has been persistently found in different environments being classified as a pollutant with some risks for human health. However, in the last years, it has been found that this compound is produced by plants or microorganisms like bacteria or fungi. This finding opened a serious debate about the origin of this compound and questioned if it is a real pollutant or a natural metabolite with some biological activities that could help us in several ways. This review tries to give some data of the different points of view about this question.